2017
DOI: 10.1016/j.chom.2017.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Basis for Increased Activity of Ebola Glycoprotein in the 2013–16 Epidemic

Abstract: Summary Ebola virus (EBOV) infection is characterized by sporadic outbreaks caused by zoonotic transmission. Fixed changes in amino acid sequence, such as A82V in the EBOV glycoprotein (GP) that occurred early in the 2013–16 epidemic, are suspected to confer selective advantage. We used biochemical assays of GP function to show that A82V, as well as a polymorphism in residue 544 identified in other outbreaks, enhances infection by decreasing the threshold for activation of membrane fusion activity triggered by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
72
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(78 citation statements)
references
References 43 publications
5
72
1
Order By: Relevance
“…The bulk of our virus studies were performed on Vero E6 cells and are in agreement with recent reports that T544I enhanced GP 1,2 -mediated entry in these cells (5,6,7). Our studies further show that the T544I mutation is a rapid and spontaneous mutation, likely not "carried" with T544 virus from clinical samples.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The bulk of our virus studies were performed on Vero E6 cells and are in agreement with recent reports that T544I enhanced GP 1,2 -mediated entry in these cells (5,6,7). Our studies further show that the T544I mutation is a rapid and spontaneous mutation, likely not "carried" with T544 virus from clinical samples.…”
Section: Discussionsupporting
confidence: 90%
“…One study has suggested that GP 1,2 containing I544 rather than T544 appeared during the EBOV Mayinga, Kikwit, and Makona outbreaks and was associated with increased disease progression and death (5). A second study suggested that the I544/T544 polymorphism might be implicated in human-to-human transmission (6). A third report suggests that the I544 residue was a tissue culture adaptation, but that study was unable to determine whether this appearance was a mutation or an outgrowth of an I544 population circulating in patients that became dominant upon growth in culture (7).…”
mentioning
confidence: 99%
“…This indicated that the early 2014 isolates, which were derived from clinical material, lacking the mutations displayed higher viral fitness, especially in human Huh-7 cells, than the later 2014 isolates with the mutations. We concluded that the in vitro growth kinetics supported the results of the animal studies, but, interestingly, they differed from the in vitro data published previously (Urbanowicz et al, 2016, Diehl et al, 2016; Dietzel et al, 2017; Wang et al, 2017). …”
Section: Resultscontrasting
confidence: 61%
“…The most recent findings in this regard include the discovery of mutations in the EBOV-Makona genome, in particular the GP and L genes, early in the outbreak that were associated with increased viral fitness in tissue culture. The authors hypothesized viral adaptation through multiple human-to-human transmission chains, leading to increased viral fitness, pathogenicity, and shedding (Diehl et al, 2016; Dietzel et al, 2017; Ueda et al, 2017; Urbanowicz et al, 2016; Wang et al, 2017). A commentary by Basler (2017) on the latest of these publications highlights the importance of these in vitro findings, but it also asks for more direct data through the evaluation of these EBOV-Makona variants in animal models, in particular nonhuman primates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation